(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The effect of the edge contraction on the theory and applications of graphs is considered in this article. A minimum number of borders must be determined to reduce the (total) dominance number in a graph. We show that at most three are the two numbers for each diagram. In view of this result, the diagrams are classified and defined by (total) dominance contractions. The next article includes the concept of flat graphs, linked graphs, path dominance, graphic cycles and few features. We have also expanded our research into reverse applications for graphics and domains.